Photography as Translation. Visual Meaning, Digital Imaging, Trans-Mediality - Gagliano, Maurizio (Recherches sémiotiques / Semiotic Inquiry, 2008)
The idea of envisaging photography through the concept of translation is based on the work of Umberto Eco on literary translation (2003) and its application to the cinema by Nicola Dusi (2003). In this article, the author seeks to clarify the terms and limits of this idea, all the while paying attention to debates surrounding the iconic sign and to issues raised by the coming of digital photography.